2022
DOI: 10.3389/fsurg.2022.889906
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Placement of Pedicle Screws - New Applications for Robotics in Spine Surgery: A Multi-Surgeon, Single-Institution Experience

Abstract: Interest in robotic-assisted spine surgery has grown as surgeon comfort and technology has evolved to maximize benefits of time saving and precision. However, the Food and Drug Administration (FDA) has currently only approved robotics to assist in determining the ideal trajectory for pedicle screw placement after extensive research supporting its efficacy and efficiency. To be considered a durable and effective option, robotics need to expand beyond the indication of just placing pedicle screws. This article a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…As demonstrated by recent literature, MIS spine surgery shows significant improvement in patient VAS, return to work time, and narcotic usage. The introduction of robot assisted techniques for MIS has been shown to increase accuracy of pedicle screw placement [ 3 , 7 , [12] , [13] , [14] , [15] ]. These procedures can be safely performed in outpatient surgery centers.…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated by recent literature, MIS spine surgery shows significant improvement in patient VAS, return to work time, and narcotic usage. The introduction of robot assisted techniques for MIS has been shown to increase accuracy of pedicle screw placement [ 3 , 7 , [12] , [13] , [14] , [15] ]. These procedures can be safely performed in outpatient surgery centers.…”
Section: Discussionmentioning
confidence: 99%
“…The global spatial navigation technique mainly involves computer or robotics-assisted spinal surgery, navigated by macroscopic imaging modalities ( Helm et al, 2015 ; Ahern et al, 2020 ). Since spinal navigation systems allow for either intra-operative imaging or pre-operative imaging with intra-operative updates, conventional navigation paradigms include intra-operative 2D fluoroscopic navigation ( Foley et al, 2001 ), pre-operative CT with manual intra-operative registration ( Nottmeier and Crosby, 2007 ), pre-operative CT with fluoroscopic registration and update, and intra-operative CT or CBCT ( Tian et al, 2011 ; Dea et al, 2016 ; Cool et al, 2021 ; Zhang et al, 2021 ; Felix et al, 2022 ; Tabarestani et al, 2022 ). Common to these solutions is their association with X-ray-like imaging (fluoroscopy or CT-based navigation solutions featuring ionizing radiation), which can harm both patient and surgeon ( Hecht et al, 2018 ; Ahern et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This precision not only minimizes tissue trauma but also reduces radiation [ 2 ]. Additionally, it has been used to complement lateral interbody fusion surgery, percutaneous iliac screw fixation, spinal endoscopy, and sacroiliac joint fusion, further enhancing its applicability across various spinal procedures [ 3 , 4 ].…”
mentioning
confidence: 99%
“…2 Additionally, it has been used to complement lateral interbody fusion surgery, percutaneous iliac screw fixation, spinal endoscopy, and sacroiliac joint fusion, further enhancing its applicability across various spinal procedures. 3,4 In the March special issue of Neurospine, Hwang et al 5 conducted a comprehensive comparative analysis of 3 pedicle screw fixation methods in their article titled "A Propensity Score-Matched Cohort Study Comparing 3 Different Spine Pedicle Screw Fixation Methods: Freehand, Fluoroscopy-Guided, and Robot-Assisted Techniques". To date, most studies have been single-or double-arm studies, with few clinical outcomes reported.…”
mentioning
confidence: 99%